Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Kostum Jersey Noto pada Siswa Sma Negeri 1 Jember - Meita Rully Mutia Sari; Yuniorita Indah Handayani; Ahmad Sauqi (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the influence of social media, product quality, brand image, customer service, and product innovation on the purchase decisions of Noto Sportswear jerseys among students of SMA Negeri 1 Jember. The objective was to analyze the partial and simultaneous effects of these variables on purchase decisions. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 72 respondents selected using purposive sampling. The data were analyzed using multiple linear regression, validity and reliability tests, classical assumption tests, coefficient of determination, t-test, and F-test with SPSS software. The results indicate that product quality, brand image, and product innovation have a positive and significant effect on purchase decisions, while social media and customer service do not have a significant partial effect. Simultaneously, all independent variables significantly influence purchase decisions. The coefficient of determination (Adjusted R² = 0.752) indicates that 75.2% of the variation in purchase decisions can be explained by the five independent variables, while the remaining 24.8% is influenced by other factors outside the scope of this study.